The importance of body-mass exponent optimization for evaluation of performance capability in cross-country skiing - Carlsson, T. (2015)
Performance in cross-country skiing is influenced by the skier`s ability to continuously produce propelling forces and force magnitude in relation to the net external forces. A surrogate indicator of the "power supply" in cross-country skiing would be a physiological variable that reflects an important performance-related capability, whereas the body mass itself is an indicator of the "power demand" experienced by the skier. To adequately evaluate an elite skier`s performance capability, it is essential to establish the optimal ratio between the physiological variable and body mass. The overall aim of this doctoral thesis was to investigate the importance of body-mass exponent optimization for the evaluation of performance capability in cross-country skiing.